OPTIMASI PROSES EKSTRAKSI KHITIN DARI CANGKANG RAJUNGAN DENGAN MENGGUNAKAN MESIN EKSTRAKSI OTOMATIS - H Hafiludin (Jurnal Kelautan, 2011)
Chitin is one of the natural polymer compound which is totally generous sufficient and most total after cellulose. This research directed to know optimisation process for the extraction of chitin from the carapax crabs by using automatic machine extraction. The research covered the activity which is appearance of utomatic machine extraction making that consist of determination level of the first extraction of optimation process. This study to analyzied the composition of raw material quality of chitin and standard of optimation of chitin extraction process. At last, this research determined continu of level optimation extraction process include study in characteristic quality of chitin. This study conducted refers to exhibit time combination during the process especially for demineralisasi and deproteinasi of chitin. Analysis for chitin extraction consist of rendemen, ash value, nitrogen value, water value, whaiteness level and deasetilasi level. The result have influence significant to examined parameter as ash value, nitrogen value, water value, whiteness level and deasetilasi level. Optimum condition obtained from demineralisasi process at 100 0C temperature for 60 minutes and deproteinasi process at 100 0C temperature for 60 minutes by 9.279% rendemen; 7.257% water; 0.6398% ash, 5.4068% total nitrogen, 50.2% whaiteness level and 21.3% deasetilasi level. Key words: Chitin, Extraction, Carapax, Crab